Identifying decarbonisation opportunities using marginal abatement cost curves and energy system scenario ensembles. (15th October 2020) - Yue, Xiufeng; Deane, J.P.; O'Gallachoir, Brian; Rogan, Fionn
Highlights: Marginal abatement cost curves are derived to compare mitigation options. Energy system analyses on scenario ensembles capture more technology details. Multiple MACCs demonstrate critical impacts of CCS and bioenergy. Abstract: The European Union has a target to reduce greenhouse gas emissions to 80% below 1990 levels by 2050 to keep global warming within 2 °C relative to pre-industrial levels. The more recent Paris climate agreement has a more ambitious target of limiting the temperature rise to well below 2 °C and the EU ambition is growing to become climate-neutral by 2050. This research explores decarbonization options using an innovative analytical approach that combines energy systems analysis and marginal abatement cost curves (MACCs). System-wide MACCs are derived using scenario ensembles from Irish TIMES energy systems model. Decomposition analysis is then used to associate decarbonization options with carbon abatement costs. In addition, energy systems analysis is carried out on the underlying scenario ensembles that are used to generate the MACCs to capture more technological details and to reflect interactions among technologies. The results show that MACCs are highly dependent on model assumptions and the availabilities of bioenergy and carbon capture and storage (CCS) technologies play critical roles. The paper also shows how key mitigation measures can be ranked and classified into categories of resilient (wind energy, CCS, electric vehicles, biofuels), tipping-point (electrifying building heating, biomass plants), and niche (ocean energy) technologies.